Analysis and extension of tree visualization - Janki Chauhan (University of Texas, Dallas, 2010)
Information visualization has always attracted human eye, as visual representation and interaction techniques allows one's mind to explore and understand large amount of information at a glance. Various information visualization techniques have been developed to show results in novel forms like graph drawing, hyperbolic tree, tree mapping and many more. Some recent development in visualization techniques has been done using fractal grammar and adoption for some existing aesthetic forms. This thesis presents how the existing algorithm of tree-mapping can be made more interactive and informative for end users. By adding level based information display, displaying communities in tree and treemap and animating the tree drawing adds more readability and reduces ambiguity of treemap. We will also discuss, what are various ways for data to be extracted and how new information can be derived from a given data set.